Factors determining organizational crisis preparedness among Malaysian manufacturers - Mohd Dahan, Hayati (2006)
Malaysia is one of the world's top trading nations. Being the biggest contributors to the economy, it is important to ensure organizational survival and increased resilience to organizational crisis. The number of industrial accidents reported in 2000 and 2001 were 41,331 and 35,642 respectively (SOCSO Annual Report, 2002). These merit immediate attention. The organizational crisis preparedness (OCP) refers to the organizational ability to anticipate, prevent, respond to and recover from organizational crisis. Based on the Protection Motivation (Maddux & Rogers, 1983) and the Systems (Hodge & Anthony, 1991) theories, this study hypothesized that organizational perception of risk, strategic orientation, slack and safety culture will positively influence OCP and that severity of crisis experience will moderate these relationships. Results of Hierarchical Regression indicate that organizational slack and safety culture are positively and significantly related to organizational crisis preparedness. However, there is no conclusive evidence that organizational perception of risk and strategic orientation are related to organizational crisis preparedness. It is also found that severity of crisis experience partially moderates the predictor-criterion relationships. Evidence from this study may create interest among organizations to look at risk variables, besides productivity and profit variables in an endeavor to ensure resilience to organizational crisis and continued organizational survival.